Analisis Teologis Perlawatan Gembala dalam Keterlibatan Jemaat pada Pelayanan Penginjilan Berdasarkan Mazmur 23:1-4 - Polden Haro; Bartolomeus Diaz Nainggolan (Danum Pambelum: Jurnal Teologi dan Musik Gereja, 2024)
This research comprehensively explores several things regarding the role of a pastor in providing visits to the people he shepherds, because this greatly influences the activities in the congregation, more specifically the evangelism that can be carried out by the congregation, so far some pastors have been lacking in terms of visits so that the impact From weak evangelistic activities in the congregation to the result of rare or even no visits by the pastors, the research methodology applied was qualitative methods and literature studies as well as exploration of suitability with the perspective of being a pastor. Data was obtained through in-depth analysis of various literary sources including texts from various journals and books, more specifically what occurred from observations of God's people in the evangelization area of the Seventh-day Adventist Church (GMAHK) South Dairi District. The findings of this research firmly state that understanding the visits of pastors should be prioritized considering that this activity has a big impact on the progress of the congregation both in terms of activities, especially in terms of the importance of evangelism in the congregation where new souls can enter into a church that is actively active.